An additional Mexican species for the Neotropical genus Eudexia Brauer and Bergenstamm (Tachinidae, Dexiini), with a redescription and lectotype fixation - Santis, Marcelo Domingos De; Couri, Márcia Souto (Zootaxa, 2025)
A redescription and photographs of the male holotype of Hystrichodexia mellea Giglio-Tos, 1893 are provided. Here this species is placed in the genus Eudexia Brauer and Bergenstamm forming a new combination for this genus, Eudexia mellea (Giglio-Tos, 1893) comb. nov. including a lectotype fixation for this species. Moreover, an updated key for all known species of Eudexia is given. Finally, a short biographical note for the type specimen collector of Hystrichodexia mellea, Auguste Sallé is included.